RANCANG BANGUN SISTEM INFORMASI TRACER STUDY BERBASIS WEB STUDI KASUS FAKULTAS ILMU KOMPUTER UNIVERSITAS INDO GLOBAL MANDIRI - Ricky Maulana Fajri (Jurnal Informatika Global)
The success of university could be measured by how much the alumni is working in the exact field of study. This could be analyzed using quistionare where the alumni filed the quistionare in the alumni website. However the data collected is not measurized how the alumni are accepted in the working place. This paper would disscuss how to implement information system of tracer study in the facultiy of computer science of the University of Indo Global Mandiri. The information system methodology would be the FAST framework as well as the ERD and DFD design mechanism, the research found out that the fast framework methodology is sufficient to develop the tracer study information system. Furthermore the information system of tracer study will present the result of tracer study by the alumni using graphical analysis for example pie chart. For the next development the researcher suggested to improve the security part of the information system. Keyword:Tracer study, ERD, DFD, Fast